Pengaruh Kualitas Produk, Persepsi Harga, dan Brand Image Terhadap Minat Beli Serum Skincare Hanasui: Studi pada Mahasiswa di Kabupaten Bogor - Agnanisa; Afif Zaerofi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine how much influence the variables of product quality, price perception, and brand image have on buying interest in Hanasui skincare serum. Using a quantitative approach with Multiple Linear Regression analysis techniques. Sampling using purposive sampling by distributing questionnaires online via Google Form to 100 students in Bogor district who use / are interested in buying Hanasui skincare serum. The findings of this study provide the results that (1) the product quality variable has a positive and significant effect on buying interest in Hanasui skincare serum for students in Bogor district. (2) the price perception variable has a positive and significant effect on buying interest in Hanasui skincare serum for students in Bogor district. (3) brand image variables have a negative and insignificant effect on buying interest in Hanasui skincare serum among students in Bogor district. Each variable simultaneously has a significant positive effect on buying interest in Hanasui skincare serum among students in Bogor district.